Vaginal repair of cesarean section scar defects: Preoperative hysteroscopic evaluation - Huihui Chen; Yizhi Wang; Hui Zhang; Xipeng Wang (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Cesarean section scar defects (CSDs) are one of the long‐term complications following cesarean section. They can be detected by transvaginal sonography, hysterosalpingography, sonohysterography and magnetic resonance imaging (MRI). Hysteroscopy is frequently used in evaluating endometrial disease. However, the description of CSDs by hysteroscopy is very limited. Only a few papers about hysteroscopy evaluation have been published. This is an exploratory study to compare hysteroscopic findings with myometrial thickness and post‐surgical outcomes. Material and methods From February 2019 to December 2020, 143 women with CSDs were enrolled in the observational study. All women suffered from abnormal uterine bleeding and were evaluated in a standardized way with hysteroscopy before vaginal surgery. Dome‐shaped CSDs could be clearly observed in all patients under hysteroscopy. We recorded the pictures of each patient under hysteroscopy and classified them. All patients underwent outpatient review at 3 and 6 months after surgery to obtain menstrual information and CSD scar size by MRI or transvaginal sonography. Results Pale mucosae in the defect were meager endometrial lining covering the surface of muscle layer, cyst lesions were some cyst lesions in the defect, increased local vascularization was a vascular tree with branching and irregular vascular distribution in defect, polypoid lesions were polypoid lesions in the defect, and serrated niches were two niches at the anterior uterine isthmus. The features of the CSDs observed under hysteroscopy were identified as five phenotypes: pale mucosae (90/143, 62.9%), cyst lesions (23/143, 16.1%), polypoid lesions (19/143, 13.3%), increased local vascularization (27/143, 18.9%) and serrated niches (7/143, 4.9%). The most common finding in scar defects under hysteroscopy was pale mucosae in the CSD. The results suggest that patients with increased local vascularization and serrated niches have a high risk of thinner residual myometrium before vaginal repair (p < 0.05). However, there was no significant difference in menstrual duration or in the outcome of vaginal repair for CSDs between these five phenotypes (p > 0.05). Conclusions Patients with the abnormal blood vessel or serration phenotypes of defects under hysteroscopy may have a thinner residual myometrium. The phenotypes of hysteroscopic findings of CSDs have no correlation with the outcome of repair.